2015
DOI: 10.1007/s10637-015-0210-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect of buparlisib, cetuximab and irradiation in wild-type or PI3KCA-mutated head and neck cancer cell lines

Abstract: Introduction In complement to anti-EGFR therapy, the targeting of PI3K/AKT/mTOR signaling pathway is of particular interest in the management of Head and Neck Squamous Cell Carcinoma (HNSCC). Here, we assess the effects of PI3K inhibition combined with anti-EGFR monoclonal antibody cetuximab and/or irradiation (RT). Material and methods Anti-proliferative effects of the combination of buparlisib (a specific PI3K inhibitor), cetuximab and RT was determined in two HNSCC cell lines (CAL33, PI3KCA H1047R-mutated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…One of the most common actionable mutations in HNSCC is PIK3CA that is a component of the PIK3/MTOR/PTEN/AKT signaling pathway involved in regulation of cell survival, growth, proliferation, metabolism, and motility and an attractive drug target in cancer . The phosphoinositide 3‐kinase (PIK3) and mammalian target of rapamycin (MTOR) signaling pathways have been found to have an important role in the pathogenesis of HNSCC and there is evidence that PIK3/MTOR antagonists are active against head and neck cancer cells . Our own studies have confirmed this activity in combination with conventional radiation treatment in low passage xenograft models of HNSCC.…”
Section: Introductionmentioning
confidence: 95%
“…One of the most common actionable mutations in HNSCC is PIK3CA that is a component of the PIK3/MTOR/PTEN/AKT signaling pathway involved in regulation of cell survival, growth, proliferation, metabolism, and motility and an attractive drug target in cancer . The phosphoinositide 3‐kinase (PIK3) and mammalian target of rapamycin (MTOR) signaling pathways have been found to have an important role in the pathogenesis of HNSCC and there is evidence that PIK3/MTOR antagonists are active against head and neck cancer cells . Our own studies have confirmed this activity in combination with conventional radiation treatment in low passage xenograft models of HNSCC.…”
Section: Introductionmentioning
confidence: 95%
“…Over 30 active clinical trials in various phases are investigating PI3K inhibitors for head and neck cancer alone. Two recent entrants BYL719 and BKM120 have resulted in pre-clinical success with on-going trials in multiple solid tumor indications including HNSCC(1618). While promise remains for PI3K inhibitors, to date there have not been any major clinical successes(19).…”
Section: Introductionmentioning
confidence: 99%
“…While newer generations of both classes with improved toxicology profiles have emerged, the goal here was to evaluate these classes of compounds in the treatment of HNSCC both as single agents and in combination with the standard of care cetuximab. While initial reports had initially indicated that mutations or other alterations along the PI3K/Akt/mTORC axis strongly predicted sensitivity to inhibitors targeting this pathway(12,28), more recent evidence suggests that this relationship is more complex(29,30), and that tumors both with and without such alterations may benefit from the addition of PI3K/mTORC to cetuximab treatment(16). In this work, we test both in vitro and in vivo HNSCC models containing both PI3K/Akt/mTORC altered and unaltered examples, to determine whether the addition of an ATP competitive kinase inhibitor can provide additional antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, unlike in-vivo models, cetuximab exerts a very low antiproliferative effect in cellular models [18,22,23]. It has already been demonstrated that the combination of anti-EGFR therapies and mTOR inhibitors resulted in a stronger growth inhibition in head and neck cancer compared with the two drugs administered alone in vitro [15,16] and in vivo [14,17].…”
Section: Discussionmentioning
confidence: 88%
“…CAL33 cells exhibit high EGFR expression (34 000 fmol/mg protein), carry a mutation on PI3KCA gene exon 20 (c.3140A > G; p. H1047R) and a p53 mutation (codon 175, CGC→CAC), and they have no intrinsic K-ras or B-raf mutations [18]. The cells were routinely maintained as monolayers in regular culture Eagle medium (DMEM) supplemented with 5 mmol/l glutamine, 1 mmol/l sodium pyruvate, and 10% fetal calf serum at 37°C in a 5% CO 2 atmosphere.…”
Section: Cell Linementioning
confidence: 99%